[Akureyri Harbor] - Streng, Evelyn Fiedler (1975)
Photograph of Akureyri Harbor. Ruster ships and boats sit along the brown harbor side and in the grey water at the bottom of the photograph. A brown mountain dotted in snow is visible in the background below grey clouds. White, rectangular buildings including one building with red roofs at the center of the photograph. Signs written in Icelandic sits along some of the buildings of the city.